Analisis Alih Kode dan Campur Kode pada Gelar Wicara Mata Najwa dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Saraswati Saraswati; Purlilaiceu Purlilaiceu; Nurul Afni Hanifah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study describes most of the speech forms that contain symptoms of code switching and code mixing as well as a description of the intentions or factors causing the symptoms of code switching and code mixing. The data source for this research is a video showing the speech title "Mata Najwa October 2021 Edition" which has been accessed on the Narasi youtube channel. The research method that the author uses is a descriptive analysis research method with data collection techniques through literature study with listening and note-taking techniques. The results of the analysis found consisted of four shows entitled soldiers of the new era, #percuma lapor polisi, servis manis bulu tangkis dan muda bersuara. The form of speech that occurs is in the form of code switching and internal code mixing from the official Indonesian language to the casual variety and Indonesian to the Medan language, while code switching and external code mixing occur from Indonesian to English. There are 248 utterances containing code switching and code mixing events. Forms of words are 159, phrases 65, clause 4 and sentence 20. The results of this study can be implied by KD 3.13 Analyzing the content of the debate (problems/issues, points of view and arguments of several parties, and conclusions).